The Vlachs – several research problems - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2015)
The aim of this article is to show the inconsistency of terminology, conceptual and substantive research on Vlachs, carried out on different areas of their residence. Seeing the need to clarify the terminology, the author proposes the use of names: “Wallachia”, “Wallachians” only in the sense of the state, in relation to the principalities of Wallachia and its people, and “Vlachia”, “Vlachs” only in the sense of ethno-society or social group. Particular attention was paid to the traps that you will encounter, examining various aspects of the life and activities of the Vlachs. The similarities on the Vlachian Right in contact with different regional conditions led to the formation of a completely new quality ethnic, legal and cultural factors that should be taken consider about conducting research. Only advanced international cooperation and joint research initiatives can yield significant progress in research about Vlachs.